Environmental Protectionism, North-South Trade, and the Uruguay Round - Sorsa, Piritta (IMF Working Papers; Working Paper, 1995)
The paper seeks to provide an overview of the present state of debate on trade, environment and the GATT for developing countries. Potential for green protectionism and relevant GATT rules are discussed in three areas: i) environmental product regulations including eco-labeling and other product measures with effects on production processes and border adjustment of environmental taxes; ii) extraterritorial use of trade measures to influence environmental behavior in other countries; and iii) the use of trade measures with international environmental agreements. The conclusion of the Uruguay Round will have a number of direct and indirect effects on trade and environment and the GATT debate on it.